2020
DOI: 10.1186/s12884-019-2717-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of companion-integrated childbirth preparation for childbirth fear, self-efficacy, and maternal support in primigravid women in Malawi

Abstract: Background: In resource-limited settings, childbirth remains a matter of life and death. High levels of childbirth fear in primigravid women are inevitable. To date, few studies have explored interventions to reduce childbirth fear in primigravid women. This study aimed to evaluate the efficacy of companion-integrated childbirth preparation (C-ICP) during late pregnancy for reducing childbirth fear and improving childbirth self-efficacy, birth companion support, and other selected pregnancy outcomes in primigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 40 publications
2
36
0
2
Order By: Relevance
“…In the present study, no significant difference was found between the regularly-attending and irregularlyattending groups in terms of the mean scores of fear, anxiety and depression. The results of studies have shown that shorter training sessions were also effective in reducing fear of childbirth and anxiety [5,27,28]. Therefore, pregnant women should be encouraged to attend as many sessions as they can if they are not able to not attend all the sessions.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no significant difference was found between the regularly-attending and irregularlyattending groups in terms of the mean scores of fear, anxiety and depression. The results of studies have shown that shorter training sessions were also effective in reducing fear of childbirth and anxiety [5,27,28]. Therefore, pregnant women should be encouraged to attend as many sessions as they can if they are not able to not attend all the sessions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, they tried to reduce their fear of childbirth by providing the necessary conditions and providing the conditions to gain postpartum social support. In previous research, planning for the day of delivery and providing the needed facilities were women’s strategies to reduce childbirth fear ( 47 , 58 , 59 ). The positive effects of social support on pregnant women during childbirth and later were indicated in the study of Spoozak et al ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 33% of pregnant women have a fear of childbirth in the last trimester of pregnancy and 11 to 14% of them experience severe fear of childbirth ( 13 ). Fear of childbirth can have many complications such as depression, abortion, increase of cesarean section ( 14 , 15 ), posttraumatic stress disorder ( 16 ) as well as negative effects on child health ( 17 19 ). Previous studies have shown that fear of childbirth is influenced by various factors such as mothers’ beliefs and personality traits ( 20 ), concerns about child health, low educational status, lack of support during pregnancy ( 21 ), having experience of sexual and physical abuse in childhood ( 22 ), and poor knowledge and interactions with medical staff ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the effectiveness of a childbirth education program during pregnancy on childbirth self-efficacy and fear of childbirth. A recent study examined the effectiveness of a companion-integrated childbirth preparation, designed to educate and support pregnant women and their birth companions, and found promising effects on fear of childbirth and childbirth self-efficacy [ 63 ]. Two randomized controlled trials on a childbirth psychoeducational program showed a reduction in fear of childbirth in the intervention group [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%